Teaching video editing and motion graphics with Photoshop - David Horowitz (Innovative Marketing)
The purpose of this paper is to examine the relationship between teaching video editing and motion graphics skills and concepts with Adobe Photoshop in a university marketing course and teaching effectiveness. Video editing and motion graphics skills and concepts were taught in a 16-week semester upper division marketing course using Adobe Photoshop. The student evaluation of teaching effectiveness data of this 16-week semester course was analyzed. The results from this analysis suggests students found learning video editing and motion graphics skills and concepts with Photoshop to be a positive learning experience. Marketing educators can teach video editing and motion graphics skills and concepts with Photoshop by following the 16-week semester course outline presented in this paper. This 16-week semester course outline contains the weekly topics and teaching materials that were used to teach the 16-week semester upper division marketing course. Finally, three sections of a master syllabus for this course, the course description, course learning outcomes, and course content are provided to help marketing educators develop and teach a similar course at their institution.